Pengaruh Beban Kerja Dan Kecerdasan Emosional Terhadap Kinerja Pegawai Pada Dinas Pertanian Dan Perkebunanan Kabupaten Bima - Muhamad Wasi’an; Jaenab Jaenab (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The aim of this research is to find out whether there is a significant influence between workload and emotional intelligence on employee performance at the Bima Regency Agriculture and Plantation Service. This type of research includes associative research, which is a method used to determine the relationship between two or more variables. The population in this study were 19 ASNs in the Secretariat Sector, 11 ASNs in the Extension Sector, 10 ASNs in the PPHP sector, 10 ASNs in the Food Crops Sector, 8 ASNs in the Horticulture Sector, 8 ASNs in the RPLPT Sector, 3 ASNs in the BPSB Sector, 25 ASNs in the in the Plantation sector and 6 ASN in Functional Positions, with a total of 100 ASN. So with this the researcher determined a sample of 80 respondents. data collection techniques using questionnaires, referring to the Likert scale, data analysis techniques using Validity and Reliability Tests, Classical Assumption Tests, Multiple Linear Regression, the results of the research are that there is a partially significant influence between Workload on Employee Performance at the District Agriculture and Plantation Service Bima, there is no partial significant influence between Emotional Intelligence on Employee Performance at the Bima Regency Agriculture and Plantation Service, and there is a simultaneous significant influence between Workload and Emotional Intelligence on Employee Performance at the Bima Regency Agriculture and Plantation Service.